2022
DOI: 10.1507/endocrj.ej21-0692
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficiency and safety of insulin degludec/aspart with insulin glargine in type 2 diabetes: a meta-analysis of randomized controlled trials

Abstract: Recent studies have found compared with insulin glargine (IGlar), insulin degludec/aspart (IDeg/Asp) may provide adequate glycemic control and prevent hypoglycemia events in type 2 diabetes mellitus (T2DM). Consequently, we performed a meta-analysis to appraise and compare the efficiency and safety of IDeg/Asp and IGlar in the treatment of T2DM. We sought the databases including PubMed, Embase, Scopus, Cochrane library to confirm related articles which inspected the effect of IDeg/Asp versus IGlar for the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the meta-analysis of studies comparing IDegAsp and IGlar, the rates of confirmed overall hypoglycemia (odds ratio [OR] = 1.59; 95% CI: 0.97 to 2.61; p=0.07; I 2 =66%) and nocturnal hypoglycemia (OR=0.54, 95% CI 0.31 to 0.94, p=0.49; I 2 =57%) were not significantly different between the treatment groups. 18 Similarly, the risk of confirmed hypoglycemia with IDegAsp, premixed insulin BID (OR 0.52; 95% CI: 0.42 to 0.65; I 2 =23.9%) and basal insulin OD (OR 0.51, 95% CI 0.27 to 0.95, I 2 =66.0) was comparable. In a meta-analysis, nocturnal hypoglycemia was significantly reduced with IDegAsp.…”
Section: Insulin Dosementioning
confidence: 91%
See 1 more Smart Citation
“…In the meta-analysis of studies comparing IDegAsp and IGlar, the rates of confirmed overall hypoglycemia (odds ratio [OR] = 1.59; 95% CI: 0.97 to 2.61; p=0.07; I 2 =66%) and nocturnal hypoglycemia (OR=0.54, 95% CI 0.31 to 0.94, p=0.49; I 2 =57%) were not significantly different between the treatment groups. 18 Similarly, the risk of confirmed hypoglycemia with IDegAsp, premixed insulin BID (OR 0.52; 95% CI: 0.42 to 0.65; I 2 =23.9%) and basal insulin OD (OR 0.51, 95% CI 0.27 to 0.95, I 2 =66.0) was comparable. In a meta-analysis, nocturnal hypoglycemia was significantly reduced with IDegAsp.…”
Section: Insulin Dosementioning
confidence: 91%
“…17 In another metaanalysis of six RCTs including 1346 patients with T2DM, a significant decrease in mean HbA1c was reported with IDegAsp OD compared with insulin glargine (IGlar) OD. 18 In another retrospective observational study, IDegAsp OD led to significantly lower HbA1c levels and FPG than basal insulin in 87 patients with T2DM in each treatment group. 19 The reduction in FPG with IDegAsp could be attributed to the long-acting effect of the IDeg analog while HbA1c reduction may be due to the prandial coverage of the IAsp analog.…”
Section: Insulin Dosementioning
confidence: 95%